CERVICOPLASTY WITH MINIMAL INCISIONS: CASE REPORT - Gouveia Gomes Camara, Patrícia; Sobreira, Talvane; Magno Ilha Algarve, Alexandre; Guimarães de Melo Nogueira, Daniela; Maria Barbosa Teixeira Canevassi, Patrícia (Health and Society, 2023)
A well-defined cervicofacial contour is desired by a growing number of patients. Among the procedures in great demand in facial surgeons’ offices are: cervicofacial tumescent liposuction and neck lifting, with satisfactory aesthetic results. Absence of perceptible scars and short recovery time are challenges for current cervical rhytidectomy. Correct diagnosis, an efficient treatment plan, refined surgical technique and postoperative care are necessary for the success of cervicoplasty. The objective of this work is to report a clinical case of surgical treatment in a patient, female, 64 years old, with aesthetic complaint in the cervical region, treated at the Visage school clinic, in Recife. For the diagnosis of increased submandibular fat associated with flaccidity of the platysmal and tissue muscles Ultrasound technology was used, cervicofacial measurements and the patient’s clinical history was collected. The multidisciplinary treatment plan included cervical liposuction, platysmal muscle suspension with mastoid anchorage, subsequent indication of the use of peeling and collagen biostimulator. Cervicoplasty was performed uneventfully and the patient received specialized physiotherapeutic follow-up, generating a high degree of satisfaction, with the result obtained as planned, with cervicofacial recontouring and minimal scarring. Thus, it can be seen that cervicoplasty using the described technique is an efficient surgical treatment, capable of solving the patient’s aesthetic complaints through oral and maxillofacial surgery.